Use of Instagram as a study tool: analysis of a profile of the biological area (Research, Society and Development, 2019)
In times of technology and information sharing, social media play an important role in the dissemination of works by brazilian universities. Instagram, a social media for sharing images and videos, can be used as tool for scientific dissemination, reaching an audience that seeks this type of information. The Laboratory of Microscopy of the Federal University of Santa Catarina - Campus Araranguá created a profile of the biological area with the username atlasmicroscopia that has as purpose the sharing of images taken in the laboratory coming from practical classes of the courses of the health area. The objective of this study is to describe the profile of the followers as well as analyze the growth of the profile in the period of one year. Atlasmicroscopia profile was logged and some data were compiled: number of likes, saved photos, profile visits and reach. Thirty two publications were selected and these were divided into two groups: Group 1(publication 1 to 16) and Group 2 (publication 17 to 32). Statistical analysis was performed between the groups with the variables: number of likes, photos saved, profile visits and reach. P